1969
DOI: 10.1007/bf02544982
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxidase deactivation to improve stability, odor and flavor of full‐fat soy flours

Abstract: Oxidation of soybean lipids catalyzed by lipoxidase was prevented by heat treatment of soybean meats, which were then ground to give a full‐fat soy flour free of rancid odor and flavors. Our previous studies showed that lipids in cracked, dehulled, soybeans rapidly oxidized after the lipoxidase system was activated by increasing moisture content to 20%. A series of experiments are reported in which various heat treatments were evaluated for effectiveness of lipoxidase deactivation. Dry heat to 212 F, steaming,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
5

Year Published

1972
1972
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 9 publications
1
26
1
5
Order By: Relevance
“…The flour in Al laminated packages were safe for 75 days in accelerated and between 75 and 90 days in ambient conditions. Mustakas et al (1969) have also reported fatty acid levels of 0.99% after 60 days on storage in LDPE bags. Generally, an increase in FFA values was more influenced by the storage temperature than humidity .The Al-laminated packages proved to be more effective for checking the FFA increase than the LDPE packages (Haridas et al 1983;Leelavathi et al 1984) as also observed in our study Nitrogen solubility index (NSI) is considered to be indicative of available nitrogen.…”
Section: Resultsmentioning
confidence: 86%
“…The flour in Al laminated packages were safe for 75 days in accelerated and between 75 and 90 days in ambient conditions. Mustakas et al (1969) have also reported fatty acid levels of 0.99% after 60 days on storage in LDPE bags. Generally, an increase in FFA values was more influenced by the storage temperature than humidity .The Al-laminated packages proved to be more effective for checking the FFA increase than the LDPE packages (Haridas et al 1983;Leelavathi et al 1984) as also observed in our study Nitrogen solubility index (NSI) is considered to be indicative of available nitrogen.…”
Section: Resultsmentioning
confidence: 86%
“…Uma diminuição da água disponível, que é quantificada pela Aa, geralmente conduz a uma diminuição nas reações deterioradoras, em um sistema alimento, devido à limitação da mobilidade dos reagentes (POTTHAST et al, 1975). Na oxidação de lipídeos, o teor de umidade tem efeitos diferentes dependendo do agente catalizador da reação, oxigênio ou enzima.…”
Section: Resultsunclassified
“…A atividade da lipoxigenase, em substratos vegetais contendo lipídeos, está estreitamente ligada às condições de umidade relativa -UR-, ou atividade de água -Aa-reinantes nesses substratos (ACKER, 1969;BROCKMANN & ACKER, 1977a;CAVALETO et al, 1966;GARDNER, 1975;GOLDOUSKII & IVANOVA, 1979;GRIMWOOD, 1971;LABUZA, 1980;MUSTAKAS et al, 1969;PRICHAVUDHI & YAMAMOTO, 1965;ZANGELMI et al, 1982).…”
Section: Introductionunclassified
“…Segundo KOCH (1968) O perfil das isoenzimas por SDS-PAGE foi de difícil identificação, tendo--se preferido o método de focalização isoelétrica para a identificação dos mutantes, como se vê na figura 2, que apresenta as bandas isoelétricas do cultivar IAC-8 e das linhagens Tohoko n 9 74, PI 86023 e PI 408251: metade do gel (segmento I) foi colorido para proteína (RIGHETTI & DRYSDALE, 1974) e metade (segmento II) para lipoxigenase (VERHUE & FRANCKE, 1972): a mutante menos L 3 apresentou fracas as bandas A, B e C; a mutante menos L 2 , a banda E forte no lugar da D, e a mutante menos L,, fracas as bandas A, D e E.…”
Section: Resultsunclassified
“…Os compartimentos do ânodo (inferior) e cátodo (superior) foram preenchidos com H 3 P0 4 0,1 M e NaOH 0,2M. A coloração das bandas para lipoxigenase, de acordo com VERHUE & FRANCKE (1972), foi feita pela imersão do gel em meio contendo 0,1% (p/v) odianisidina, 0,1% (p/v) ácido linoléico e 10% (v/v) etanol em tampão NaPi pH 7,0 0,1 M. Para prqteína, pela imersão em meio contendo 0,05% de Coomassie blue e 0,1% de CuS0 4 em ácido acético-etanol-H 2 0 (RIGHETTI & DRYSDALE, 1974).…”
Section: Determinação Qualitativaunclassified